KERAGAMAN DAN HERITABILITAS KETAHANAN TEBU POPULASI F1 TERHADAP PENYAKIT BERCAK KUNING DI PT GUNUNG MADU PLANTATIONS LAMPUNG - Nyimas Sa’diyah; Titik Nur Aeny (Universitas Lampung, 2012)
The objective of this study was to estimate variability and heritability of yellow spot disease characters of 12 sugarcane genotypes. The experiment was conducted on sugarcane field in PT Gunung Madu Plantations (PT GMP), Gunung Sugih Central Lampung, from January to May 2009. The treatments consisted of 12 F1 sugarcane genotypes resulted from the previous crossing of several existed varieties done by PT GMP research and development. The variability was estimated using the method from Anderson and Bancroft (1952) and the heritability was estimated based on the method from Allard (1995). The results showed that the severity of sugarcane yellow spot disease in the PT GMP Lampung showed high variability but low heritability (0.21). Out of 12 tested sugarcane genotypes, G12 has the highest resistance showed by the lowest disease severity.